2005
DOI: 10.1111/j.1601-0825.2005.01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved oral hygiene and Candida species colonization level in geriatric patients

Abstract: The OH protocol led to an overall decrease in Candida spp. colonization, a significant reduction in the number of candidiasis and an improvement in the level of oral and denture hygiene but vigilance is still necessary concerning OH care and the initial training of staff in specific care of the mouth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
3
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 37 publications
6
39
3
10
Order By: Relevance
“…This study demonstrated a strong association between poor denture hygiene and oral candidal colonization. These findings are similar to studies conducted by Azmi and Grimoud, 1,12 and tends support to research that plaque accumulation on the denture surface may create an appropriate environment for yeast growth.…”
supporting
confidence: 80%
“…This study demonstrated a strong association between poor denture hygiene and oral candidal colonization. These findings are similar to studies conducted by Azmi and Grimoud, 1,12 and tends support to research that plaque accumulation on the denture surface may create an appropriate environment for yeast growth.…”
supporting
confidence: 80%
“…Th is is due to the role of saliva in inhibiting oral microbial colonization 11,15 . Th e mouth is a reservoir of yeasts and these fungi can be frequently isolated without related pathologic changes to the epithelium 29 . Th e incidence of yeast colonization in clinically normal mouth of healthy adults ranges from 3% to 48% 30 .…”
Section: Discussionmentioning
confidence: 99%
“…27 29) Furthermore, if patients have lowered immunity due to an underlying disease or medication, Candida albicans or Candida glabrata may be identified, even when no conspicuous lesion is noted. 30) In the present study, although there were no noticeable symptoms of candidiasis in the mouth or on the pharyngeal mucosa of subjects, Candida The present study did not take into account the immune competence of subjects. Further research should be conducted to closely examine the relationship between oral health problems and the identification of Candida species, using a larger number of subjects.…”
Section: )mentioning
confidence: 93%
“…22) Nevertheless, a candidal infection in the oral cavity may cause angular stomatitis and oral candidiasis. 30) Since uniformed nursing procedures for intubation were implemented in the ICU to prevent damage to the soft tissue, the lips-related and angular symptoms were presumably caused by an increase in Candida species in the mouth, and it took a long period of time to improve them as ordinary oral care could not reduce the fungus.…”
Section: )mentioning
confidence: 99%